Editorial - Alberca-Sialer, Fabrizio Augusto (2025)
The issue of Turismo y Patrimonio presented here contains articles related to heritage, tourism, nature, and the environment. Through this journal, these manuscripts become part of the international discussion with the aim of fostering, in the long term and as previously stated, a better understanding—and, why not—peace. Dear reader, as with every edition we have published, the articles presented below have undergone a rigorous peer-review process, carried out by distinguished subject-matter experts with experience in scientific publishing.